Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

2\sqrt{3}+x-\sqrt{3}x=-2
Subtract \sqrt{3}x from both sides.
x-\sqrt{3}x=-2-2\sqrt{3}
Subtract 2\sqrt{3} from both sides.
\left(1-\sqrt{3}\right)x=-2-2\sqrt{3}
Combine all terms containing x.
\left(1-\sqrt{3}\right)x=-2\sqrt{3}-2
The equation is in standard form.
\frac{\left(1-\sqrt{3}\right)x}{1-\sqrt{3}}=\frac{-2\sqrt{3}-2}{1-\sqrt{3}}
Divide both sides by 1-\sqrt{3}.
x=\frac{-2\sqrt{3}-2}{1-\sqrt{3}}
Dividing by 1-\sqrt{3} undoes the multiplication by 1-\sqrt{3}.
x=2\sqrt{3}+4
Divide -2-2\sqrt{3} by 1-\sqrt{3}.